Peningkatan Keinovatifan Guru Melalui Penguatan Kepemimpinan Transformasional dan Efikasi Diri - Cahyo, Fatkhurrohman Dwi; Hidayat, Rais; Herfina, Herfina (Universitas Pakuan, 2024)
INCREASING TEACHER INNOVATIVENESS THROUGH STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND SELF-EFFICACYThis research aims to find efforts that can be made to increase teacher innovativeness by studying its relationship with Transformational Leadership and Self-Efficacy. The population of this study was 170 teachers, with a total sample of 120 Integrated Islamic Elementary School teachers in Cibinong District, whose determination used the Slovin formula with an error tolerance of 5%. Data was collected using instruments in questionnaires and analyzed using descriptive and inferential statistical analysis. The research results show three positive and very significant relationships. First, there is a positive and very significant relationship between the Transformational Leadership variable and Teacher Innovativeness, with a correlation coefficient of 0.818. Second, a positive and very significant relationship exists between Self-Efficacy and Innovativeness, with a correlation coefficient of 0.716. Third, there is a positive and very significant relationship between Transformational Leadership and Self-Efficacy and Teacher Innovativeness with a correlation coefficient of 0.854.